The overlap between binge eating disorder and substance use disorders: Diagnosis and neurobiology - Schreiber, Liana R. N. (Akadémiai Kiadó, 2013)
Background and aims: Binge eating disorder (BED) is a relatively common condition, especially in young adult females, and is characterized by chronic over-consumption of food resulting in embarrassment, distress, and potential health problems. It is formally included as a disorder in DSM-5 for the first time, an acknowledgement to its debilitating nature. This article explores the overlap between binge eating disorder and substance use disorders (SUD). Methods: The bibliographic search was a computerized screen of PubMed databases from January 1990 to the present. Binge eating disorder, substance use disorder, binging, obesity, food addiction, comorbidity, dopamine, opioid, serotonin, glutamate, and pharmacological treatment were the keywords used in searching. Results: BED shares similar phenomenology to SUD, including significant urges to engage in binging episodes, resulting in distress and impairment. Similar neurobiological pathways are found in both BED and SUD and medications based on similar neurobiology have been examined for both disorders. A subset of individuals with BED may have a “food addiction”, but there is no clinical agreement on the meaning of “food addiction”. Exploring the relationship between BED and obesity may also shed light on the extent to which BED can be viewed as an addiction. Conclusions: Overall, nascent research regarding BED and SUD suggests an overlap between these disorders, but there are discrepancies between these two disorders that need further exploration.